PS01.153: MEDIASTINOSCOPIC ESOPHAGECTOMY FOR THE PATIENT OF ESOPHAGEAL CARCINOMA WITH CHRONIC OBSTRUCTIVE LUNG DISEASE(COPD). (14th September 2018) - Ohara, Masanori; Yamabuki, Takumi
Abstract: Background: Respiratory failure is one of fatal postoperative complication after esophagectomy. The patient with COPD is tendency to contraindication of esophagectomy. Thoracoscopic esophagectomy preserve respiratory function comparing with open esophagectomy. We suppose to preserve more respiratory function with mediasinoscopic esophagectomy. Methods: 77-year-old male. He had home oxygen therapy(HOT) by 1 liter oxygen per minute. Diagnosis was lower esophageal carcinoma with metastasis of upper mediastinum and cardiac lymphnode. We performed mediasinoscopic esophagectomy with lymphnode dissection. Results: Pathological findings revealed adenocarcinoma with metastasis of cardiac and bilateral laringial nerve lymphnode. He recovered after one week mecanical ventilation. He discharged after rehabilitation. Conclusion: The patient with COPD has high risk of esophagectomy. However, we suppose mediastinoscopic esophagectomy is one of the hopeful option incase of sufficient informed consent. Disclosure: All authors have declared no conflicts of interest.